Core food intakes of Australian children aged 9–10 years: nutrients, daily servings and diet quality in a community cross‐sectional sample. Issue 4 (29th March 2016) - Whitrow, M. J.; Moran, L.; Davies, M. J.; Collins, C. E.; Burrows, T. L.; Edwards, S.; Moore, V. M.
Abstract: Background: The present study aimed to evaluate core food intakes in 9–10‐year‐old Australian children by considering adequacy of nutrient intakes, comparing servings of core food groups with Australian recommendations and scoring overall diet quality. Methods: Children from an established community‐based cohort study completed a semi‐quantitative food frequency questionnaire. Daily intakes of energy, macronutrients, micronutrients, servings of core (i.e. nutrient‐rich) foods and a diet quality index were calculated and compared with appropriate standards. Sex and socio‐economic differences were examined. Results: The 436 children participating were from low to high socio‐economic status families. As a group, over half of the children met estimated average requirements for key macro‐ and micronutrients, with the exception of fibre (inadequate in 41% of boys and 24% of girls). Children obtained 55% of their daily energy from core foods. Most children had fewer than the recommended servings of vegetables (91%) and meat/alternatives (99.8%), whereas boys generally ate fewer servings of grains and cereals than recommended (87%), and girls ate fewer servings of dairy (83%). Diet quality scores indicated room for improvement (median score of 26 for boys and 25 for girls, out of a maximum of 73 points). Conclusions: As a group, a large proportion of children were able to meet their daily nutrient requirements. However, achieving this through noncore foods meant that diets were high in salt, saturated fat and sugar; more servings of core foods and greater dietary diversity would be preferable. These results suggest that families need more support to optimise dietary patterns of children in this age group.